GAMBARAN PERAN BYSTANDER DALAM PERILAKU BULLYING: STUDY DESKRIPTIF PADA SISWA MTS - Reyhani Lady Mauna; Yeni Karneli; Miftahul Fikri; Azmatul Khairiah Sari (STKIP Subang, 2026)
Bullying in schools involved bystanders whose responses could influence whether bullying continued or stopped. This study aimed to describe the roles of bystanders in bullying behavior among students at MTsN 1 Padang. A quantitative descriptive design was employed. The population consisted of 352 students, and 194 students were selected using proportionate stratified random sampling. Data were collected using a bystander role scale that measured four dimensions: assistant, reinforcer, outsider, and defender. The data were analyzed using descriptive statistics. The findings showed that the defender role was the most dominant, followed by outsider, reinforcer, and assistant. Most students tended to protect victims when witnessing bullying incidents. These findings provide a basis for guidance and counseling teachers to develop programs that strengthen prosocial behavior and encourage students to take positive action in bullying situations.